TERT promoter wild-type glioblastomas show distinct clinical features and frequent PI3K pathway mutations - Williams, Erik A.; Miller, Julie J.; Tummala, Shilpa S.; Penson, Tristan; Iafrate, A. John; Juratli, Tareq A.; Cahill, Daniel P. (Acta neuropathologica communications, 2018)
TERT promoter ( TERT p) mutations are found in the majority of World Health Organization (WHO) grade IV adult IDH wild-type glioblastoma ( IDH -wt GBM). Here, we characterized the subset of IDH -wt GBMs that do not have TERT p mutations. In a cohort of 121 adult grade IV gliomas, we identified 109 IDH -wt GBMs, after excluding 11 IDH -mutant cases and one H3F3A - mutant case. Within the IDH -wt cases, 16 cases (14.7%) were TERT p wild-type ( TERT p-wt). None of the 16 had BRAF V600E or H3F3A G34 hotspot mutations. When compared to TERTp mutants, patients with TERT p-wt GBMs, were significantly younger at first diagnosis (53.2 years vs. 60.7 years, p = 0.0096), and were more frequently found to have cerebellar location ( p = 0.0027). Notably, 9 of 16 (56%) of TERT p-wt GBMs contained a PIK3CA or PIK3R1 mutation, while only 16/93 (17%) of TERT p-mutant GBMs harbored these alterations ( p = 0.0018). As expected, 8/16 (50%) of TERT p-wt GBMs harbored mutations in the BAF complex gene family ( ATRX, SMARCA4 , SMARCB1 , and ARID1A ), compared with only 8/93 (9%) of TERT p-mutant GBMs ( p = 0.0003). Mutations in BAF complex and PI3K pathway genes co-occurred more frequently in TERT p-wt GBMs ( p = 0.0002), an association that has been observed in other cancers, suggesting a functional interaction indicative of a distinct pathway of gliomagenesis. Overall, our finding highlights heterogeneity within WHO-defined IDH wild-type GBMs and enrichment of the TERT p-wt subset for BAF/PI3K-altered tumors, potentially comprising a distinct clinical subtype of gliomas.